Mirativity in Persian - Rasekh-Mahand, Mohammad (Journal of Iranian Linguistics, 2024)
Mirativity, as a distinct grammatical category, could be marked by different markers and strategies. In this paper, it is argued that, contrary to previous studies, Persian marks mirativity by using morphosyntactic forms. Three different grammatical tools are identified. First, it has a sentence final clitic ‘=ā’ used as mirative marker on its own right. It indicates that the information is newsworthy, unexpected and surprising. Second, the sentence final particle ’ke’, among its different functions, marks mirativity, as well. Third, using different perfect verb forms in Persian is a mirative strategy, which is strongly connected to indirect evidentiality. The data from Persian widens our understanding of mirativity cross-linguistically, showing that a language could have different ways to mark it simultaneously.